The surgical management of necrotising enterocolitis (NEC). (June 2016) - Thakkar, Hemanshoo Sudhir; Lakhoo, Kokila
Abstract: Necrotising enterocolitis (NEC) is a neonatal surgical emergency. At its early stages, the management of NEC is largely medical using broad-spectrum antibiotics, gut rest and total parental nutrition. The only absolute indication for surgery is an intra-abdominal perforation. There are several relative indications for surgery based on clinical, biochemical and radiological parameters. Once the decision to intervene is made, several approaches may be taken. Peritoneal lavage can be used as a salvage procedure or definitive management in some cases. The most common approach taken is bowel resection with enterostomy formation. There is a role for primary anastomosis of bowel in limited NEC. In severe, multi-focal NEC a high diverting jejunostomy or "clip and drop technique" can be used. Laparoscopy has a limited role and is not widespread. The surgical complications of NEC include stoma related morbidity, anastomotic leak/stricture and short-bowel syndrome. Long-term data on neurodevelopmental outcomes is sparse but the present literature is suggestive of a negative impact in cases of surgically managed NEC.